2001
DOI: 10.1007/s001470100336
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cyclosporine in monkeys after oral and intramuscular administration: relation to efficacy in kidney allografting

Abstract: In cynomolgus and rhesus monkeys, the dose-normalized exposure of cyclosporine administered orally as microemulsion preconcentrate (Neoral) was lower than that upon intramuscular administration. For oral administration, mean values ( f SD) of C,,,, 24-h area-under-the curve (AUC) and 24-h trough level, all normalized for a 1 mg/kg dose, were 20 k 9 ng kgfmg ml, 210 k 70 ng h kg/mg ml and 2.6 * 0.9 ng kg/mg ml, respectively.For intramuscular administration, levels were about 5.5-fold, 9-fold and 22-fold higher.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
5
13
0
Order By: Relevance
“…The average concentration is comparable to the IC 50 values of CsA obtained from monkey hepatocytes and cOATP-expressing HEK-293 cells. The CsA systemic exposures obtained in this study were comparable to those in patients at a therapeutic dose (Novartis, 2005) and in monkeys at 50 and 100 mg/kg (Schuurman et al, 2001).…”
Section: Resultssupporting
confidence: 67%
“…The average concentration is comparable to the IC 50 values of CsA obtained from monkey hepatocytes and cOATP-expressing HEK-293 cells. The CsA systemic exposures obtained in this study were comparable to those in patients at a therapeutic dose (Novartis, 2005) and in monkeys at 50 and 100 mg/kg (Schuurman et al, 2001).…”
Section: Resultssupporting
confidence: 67%
“…In the same model, median survival times of 59 days and 56 days were reported with SDZ-RAD and sirolimus, respectively (26). Whereas cyclosporine treatment produced long term, rejection-free survival (Ͼ100 days) (26,27) when animals from the Philippines were used, animals originating from Mauritius (such as those used in the current study) demonstrated significantly poorer survival with a median graft survival of 26 days (28). In the current series, 5 of 18 animals were euthanized with a normal renal function as reflected by normal serum creatinine and blood urea nitrogen levels.…”
Section: Discussionmentioning
confidence: 80%
“…2), although this can be less severe in nonhuman primates than in the clinical situation. In our experience in cynomolgus monkeys receiving a kidney transplant, long-term exposure at reasonably high levels is well tolerated without overt renal side effects (average 24 h trough levels upon oral CsA monotherapy ranging between 250 and 700 ng/mL; in one animal upon intramuscular administration up to 1000 ng/mL; Schuurman et al, 2001). In mice CsA acts in concert with STZ in evoking pancreas toxicity (Sai et al, 1988) and potentiates the action of STZ in producing diabetes (Sestier et al, 1985).…”
Section: Discussionmentioning
confidence: 95%